Distribution of resources and quality of life in oncology: ethical considerations - Palazzani, L.; Mele, V.; Sgreccia, Elio (Medicina e Morale, 1992)
The article examines the ethical criteria of the distribution of resources in oncology from two points of view, that is: macro-allocation (allocation in different health services) and micro-allocation (decisions about who has to obtain available resources). In particular it underlines the role of the consideration of quality of life in social utilitarianism, libertarian individualism and contractualism. Through the criticai analysis of these trends, the article points out the relevant contribution of personalism.